PERANCANGAN VISUAL IDENTITY BIKA SI MARIANA KOTO BARU TANAH DATAR - YUNESA MILAHENDRI, Henra Afriwan, S.Sn., M.Sn. Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Bika Si Mariana is widely known to the public, but Bika Si Mariana does not yet have a visual identity that forms an image that is needed by companies to attract the attention of customers or buyers.The objectives to be achieved in the design of Bika Si Mariana's visual identity is to provide a visual identity and identity of Bika Si Mariana Koto Baru Tanah Datar, which will function as (1) Designing a visual identity to be able to display Bika Si Mariana's identity, (2) Informing to the public if Bika Si Mariana has its own characteristics, (3) Designing a visual identity that attracts consumers to know and buy Bika Si Mariana Products, (4) As a promotion for the creation of a visual identity in the form of a logo from Bika Si Mariana can be applied to various media supporters such as posters, x-banners, aprons, packaging, costumes, stamps, stickers, invoices and mugs. Stages of design starts from data collection, analysis and design. The process of collecting data through interview observation and documentation, while the data analysis process uses the 5W + 2H analysis method.Keywords: Visual Identity, logo, Bika Si Mariana.